Instagram's impact on sharia economic law literacy in the digital age and Indonesia's sharia economy strengthening - Haanurat, A. Ifayani; Vedianty, Adinda Syalsabilla Aidha; Tollentino, Sahay Amrita (CV. Bimbingan Belajar Assyfa, 2023)
The emergence of the Fourth Industrial Revolution has revolutionized information accessibility, especially through social media platforms such as Instagram. This study investigates the role of Instagram in increasing Sharia economic law literacy and its subsequent impact on strengthening the Sharia economy in Indonesia. Using an ethnographic approach, this research explores four Instagram accounts dedicated to Contemporary Fiqh Muamalah and Maliyah, testing their effectiveness in educating users about Sharia economic principles before carrying out trading activities. Data was collected through systematic observation and documentation studies, followed by descriptive and qualitative analysis. The findings show that Instagram functions as an important tool in spreading Sharia economic law, thus making a significant contribution to the growth and stability of the Sharia economy in Indonesia. Furthermore, this research highlights the importance of digital literacy in Sharia financing to encourage peace and economic development in Indonesia.